Aliphatic dithiocarboxylic acids: New adsorbates for soft lithographic patterning - Lee T.-C. (2014)
This paper describes an initial evaluation of the use of aliphatic dithiocarboxylic acids (ADTCAs) as transient protecting agents in soft lithographic patterning, also known as microcontact printing (μCP). Surfaces micropatterned using ADTCA-based inks (C10-C16) were compared to that patterned using a standard hexadecanethiol ink. The patterns were characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM). Etch-removal studies of SAM-coated gold substrates found that the longer chain-length ADTCAs (C13-C16) provide better protection against etching than the shorter chain-length ADTCAs (C10-C12). These studies demonstrate that ADTCA-derived SAMs can be used as effective resists for soft lithographic applications. © 2008 Elsevier B.V. All rights reserved.